Article 251 of the Kitab Undang-Undang Hukum Dagang is Related to the Principle of Utmost Good Faith - Samuel Frans Boris Situmorang (Manunggal Halim Jaya, 2026)
Correct notification of the insurance object by the insured to the insurer in an insurance law is very important. The conditions for the validity of the insurance agreement are 1320 of the Kitab Undang-Undang Hukum Perdata, Article 250 of the Kitab Undang-Undang Hukum Dagang, and Article 251 of the Kitab Undang-Undang Hukum Dagang. So, Article 251 of the Kitab Undang-Undang Hukum Dagang is a condition for the validity of an insurance agreement. The author agrees to the Judge's Consideration and Dictum of the Constitutional Court of the Republic of Indonesia Number: 83/PUU-XXII/2024. The decision is in accordance with the principle of utmost good faith. However, Article 251 of the Kitab Undang-Undang Hukum Dagang is more related to the principle of utmost good faith, according to the author, in line with the opinion in the book Prof. H. Man Suparman Sastrawidjaja, S.H., S.U and Endang, S.H, namely through a change in the law, namely Article 251 of the Kitab Undang-Undang Hukum Dagang, changes are made in such a way that the act of rejecting claims based on Article 251 of the Kitab Undang-Undang Hukum Dagang must be tested against Article 1338 Paragraph (3) of the Kitab Undang-Undang Hukum Perdata (principle of good faith / utmost good faith). The research method in this paper is normative descriptive that provides data/overview by analyzing using legal principles, examining the systematics of laws and regulations.